Halal Food Standards for Food Security and Agricultural Sustainability: A Comparative Study of East Africa and Indonesia - Alwy Ahmed Mohamed; Abdulrohim E-sor; Muhammad Ndow; Qudra Bezibweki (Walidem Institute and Publishing (WIP), 2025)
Objective: With a comparative focus on East Africa and Indonesia, this study attempts to explore how halal food standards contribute to agricultural sustainability and food security. In addition to addressing consumer trust, market access, and sustainable farming practices, the study looks at how halal certification regimes affect food production, distribution, and consumption. Theoretical framework: Islamic economic ideas and food systems theory serve as the study's foundation. While Islamic halal standards place a strong emphasis on ethical food production, consumer protection, and socioeconomic justice, food systems theory offers a perspective through which to view the relationships between production, distribution, and consumption. Literature review: Prior research emphasises how halal requirements affect market access, food safety, and moral consumption. While East African nations are still in the early stages of adoption due to issues like inadequate regulatory infrastructure, lax enforcement, and poor consumer awareness, Indonesia has gained widespread recognition for its extensive halal certification framework. Methods: This study uses a qualitative comparative methodology, examining institutional practices, policy documents, and sociocultural contexts in Indonesia and East Africa. In order to evaluate the efficacy and effects of halal standards on food security and agricultural sustainability. Results: The results show that Indonesia has constructed a strong halal certification system that guarantees food quality, helps smallholder farmers, and fosters international trade. East African nations, on the other hand, are still in the early phases of creating halal frameworks and are facing obstacles like insufficient regulatory monitoring, low consumer awareness, and shoddy enforcement procedures. Implications: The report emphasises how crucial it is to match halal certification with consumer protection, regional trade integration, and sustainable farming methods. In addition to easing access to expanding international halal markets, policymakers and industry stakeholders can use halal standards to benefit smallholder farmers, advance ethical food production, and improve food security. Novelty: This study's innovation is its comparative cross-regional analysis, which shows how halal food standards can be used as a tool for economic integration, sustainable agriculture, and food security in a variety of socioeconomic contexts.